Gene expression of chemokines CX3CL1 and CXCL16 and their receptors, CX3CR1 and CXCR6, in peripheral blood mononuclear cells of patients with relapsing-remitting multiple sclerosis – A pilot study - Stojković, Ljiljana; Stanković, Aleksandra; Životić, Ivan; Dinčić, Evica; Alavantić, Dragan; Živković, Maja (Vojnosanitetski pregled, 2021)
Background/Aim. In vitro and in vivo studies show that CX3CL1 and CXCL16 chemokines and their specific receptors, CX3CR1 and CXCR6, respectively, mediate mechanism of neuroinflammation during the pathogenesis of multiple sclerosis (MS). The aim of this study was to investigate relative messenger ribonucleic acid (mRNA) levels of CX3CL1, CXCL16, CX3CR1 and CXCR6 in peripheral blood mononuclear cells, as potential molecular markers of relapsing-remitting (RR) MS. Methods. The study included 43 unrelated RR MS patients, 20 of them with clinically active disease (relapse) and 23 with clinically stable disease (remission), and 28 unrelated healthy subjects as controls. Real-time polymerase chain reactions (PCR) were performed using TaqMan® gene expression assays. Relative expression (mRNA) level of each target gene in each sample of peripheral blood mononuclear cells was calculated as the mean normalized expression. Results. The levels of CX3CR1 mRNA were significantly higher in clinically active RR MS patients compared to controls [fold change = 1.38, p (Mann-Whitney U test) = 0.009], and significantly lower in clinically stable vs active RR MS patients [fold change = -1.43, p (t-test) = 0.03]. Stable RR MS patients had significantly higher CXCL16 mRNA levels than controls [fold change = 1.33, p (Mann-Whitney U test) = 0.006]. A trend of increased CXCR6 gene expression was found in active RR MS patients compared to controls [fold change = 1.23, p (Mann-Whitney U test) = 0.08]. In either active or stable RR MS patients there were no significant correlations of the clinical parameters with expression levels of the target genes. Conclusion. The current results show that increased CX3CR1 mRNA levels in peripheral blood mononuclear cells could represent a proinflammatory molecular marker of clinically active RR MS.